Bacterial vaginosis: prevalence diagnosis and a health center - Méndez, Maritza (2015)
Objective: To evaluate the prevalence of bacterial vaginosis in women of a rural population with vaginal discharge. Design: Prospective, transversal, analytical study. Material and Methods: Vaginal secretion samples were taken from 100 patients with vaginal discharge, and microbiologic analysis and Amsel‘s criteria for bacterial vaginosis diagnosis were applied. Results: Bacterial vaginosis was found in 33% of patients that fulfilled at least 3 of the 4 Amsel‘s criteria, candidiasis in 15%, trichomoniasis in 4% and mixed culture in 5%. Clue cells and the amine test allowed us to identify the largest percentage of patients with bacterial vaginosis; likewise, the presence of clue cells alone, clue cells + odor and odor + pH had high positive and negative predictive value. Vaginal discharge sensitivity is low. Conclusions: Bacterial vaginosis is the most common vaginal infection among reproductive age women from Quilmaná City, representing at least one third of such infections. Diagnosis can be done in ambulatory clinical practice applying only two of the Amsel’s criteria, like amine test plus vaginal secretion pH.